2020
DOI: 10.3390/su12229362
|View full text |Cite
|
Sign up to set email alerts
|

Inner-Self vs. Outer-Self and Socially Responsible Product Consumption

Abstract: This paper investigates how two fundamental consumer characteristics, self-esteem (inner-self) and status seeking (outer-self), influence consumers’ purchasing behaviors of CSR (Corporate Social Responsibility) products via two mediating effects: brand image and self-enhancement. In particular, we analyze these effects in two different CSR domains: environmental and social. By doing so, we are able to verify the underlying mechanisms of how different types of consumers respond to various CSR promotions. We pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
8
0
1
Order By: Relevance
“…Finally, this study only explored a single piece of CSR information, i.e., conflict metals. Prior research suggests that environmental CSR differs from social CSR in the way each type influences consumers [34]. Future research could investigate the interplay between CSR and evaluability to gain deeper insights into the distinctions that may exist between different CSR types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study only explored a single piece of CSR information, i.e., conflict metals. Prior research suggests that environmental CSR differs from social CSR in the way each type influences consumers [34]. Future research could investigate the interplay between CSR and evaluability to gain deeper insights into the distinctions that may exist between different CSR types.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, consumers indicated greater willingness to pay for computers manufactured by ethical companies [31], athletic shoes manufactured by companies that conduct CSR activities [32], and fair-trade coffee [33]. In this study, we particularly focus on the trade-off relationship between CSR and price because, although CSR is often identified as an effective marketing tool, its commercial effectiveness remains debatable [34].…”
Section: Introductionmentioning
confidence: 99%
“…Much prior research regarding the intention-action gap of environmentally friendly consumption focuses on strong intentions and weak action, explaining why people hesitate to buy a product with an environmentally friendly attribute and proposing ways of mitigating hesitancy. Some suggested making sustainable behavior the default, assisted by prompt and feedback [3], while others proposed the activation of status motives or encouraging consumers to make purchase decisions in a conspicuous context [4,5]. For example, a study showed that when the package color was environmentally friendly (e.g., blue), consumers' preferences for environmentally friendly products increased as the purchase context became more conspicuous [31].…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed solution was to activate status motives, based on experimental findings that among participants who read a story in which they have an opportunity to receive a desirable promotion their desire for a dishwasher with a recirculating water system that would save water increased [4]. The second solution was supported by a recent survey showing that the more strongly people sought status, the greater their purchase intention was for a 100%-recycled notebook [5].…”
Section: Introductionmentioning
confidence: 99%
“…First, Chinese enterprises still treat the performance of social responsibility as a type of “advertisement” marketing behavior [ 12 ], considering that association produced by CSR can deliver altruistic value of enterprises in a warmhearted manner, that is, satisfying customer and social demands, which is beneficial in obtaining brand reputation [ 13 ] and then enhancing brand value [ 14 , 15 ]. Second, brand fulfilling social responsibility is favored by consumers, which can establish a strong emotional connection with consumers [ 16 ] and bring high market share to enterprises [ 17 ], which can positively influence brand value. Furthermore, the source of brand value is its future profitability, and it is the willingness and motivation of consumers to continuously pay for brand beyond product or service premium [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%